Application of a Two-Stage Anaerobic System from Guava Processing Waste to Bioenergy - De Carvalho, Romário P. [UNESP]; Maintinguer, Sandra Imaculada [UNESP] (SAGE Publications, 2022)
The application of maximum feedstock capacity through the treatment of organic wastes generated in the industrial chain is necessary for environmental preservation. Agro-industrial waste, such as from fruit processing, can be treated by anaerobic digestion with bioenergy generation. This study aimed to evaluate the consumption of guava processing waste on hydrogen (H2) and methane (CH4) production in a two-stage anaerobic system under four different conditions (substrate/inoculum ratios of 0.67, 1.0, 2.0, and 3.0 g COD g-1 VS). Bio-H2 (5.26-3.50 mL H2 g-1 VS) and bio-CH4 (266.27-104.67 mL CH4 g-1 VS) were produced, with consequent high efficiencies of organic matter (75-90% to total COD) and carbohydrates (98-99%) removals. Paraclostridium and Clostridium genera were used in ethanol, acetic, propionic, and butyric acids generation in the first stage, and these metabolites were consumed in the second stage. The estimated energy yields of the two-stage system were 1.1-2.7 kJ kg-1 residue. Guava residues can be recovered by application in anaerobic processes for the generation of biofuels and other added-value bioproducts.
Keywords: anaerobic digestion; Fruit processing waste; hydrogen; methane; Paraclostridium